An evaluation of the impact of "out-of-season" vegetable production on nitrogen leaching : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management at Massey University, Palmerston North, New Zealand - Stout, Michaela Jayne (Massey University, 2021)
Nitrogen (N) leaching is a major driver of freshwater degradation in New Zealand. This has resulted in a strong regulatory focus on reducing N leaching rates from intensive land uses in recent years. Of all intensive land uses, vegetable cropping generally has the highest rate of N leaching per land area (Di & Cameron, 2002). Given that the vegetable cropping industry is worth $6.39 billion annually, and the public health necessity of maintaining the supply of fresh vegetables, there is a growing priority to research and develop methods to reduce the N leaching footprint of vegetable production to ensure the future viability of the industry (HortNZ, 2020). It is often claimed that the need to produce vegetables crops “out-of-season” to satisfy consumer demand for year-round availability of vegetables is one of the reasons that vegetable farms leach such large quantities of N. The validity of this claim has not been explored in a New Zealand context. This thesis aims to fill this research gap by investigating and comparing the annual N leaching rates under “in-season” and “out-of-season” vegetable production, using a case study approach. The case study is an intensive vegetable cropping block in the Horowhenua, a region renowned for intensive vegetable production. The case study will be focused on two varieties of the Brassica oleracea L. species: broccoli and cauliflower. The case study and research question will be investigated using a modelling approach, making use of APSIM and Overseer. A modelling approach was used due to the lack of available field-based data, and the impracticality of collecting field-based data within the time constraints of this thesis. The effect of “out-of-season” production on N leaching was also contrasted with the effect of two good management practices (GMPs): the use of catch crops and minimum tillage. A gross margin analysis was also performed to gauge the financial viability of a seasonal production regime. Contrary to expectations, the annual N leaching rates (as kg N/ha) under an “out-of-season” production regime were on average 39% lower than the N leaching rates under an “in-season” production regime. This difference was largely driven by higher rates of soil inorganic N through the autumn/winter period (i.e., when most of the annual N leaching occurred) under “in-season” production. The greater quantity of soil inorganic N could be traced to higher quantities of residue N left behind by “in-season” production of broccoli and cauliflower, which was partly explained by higher yields. As such, the key to determining the effect of seasonal production on N leaching is less about the classification of what is “in” season and what is “out” of season, and more about understanding the ability for crops to generate and/or take-up high levels of inorganic N over the autumn/winter period. While the production of the study crops “out-of-season” led to a reduction in the N leaching rate on a per hectare basis, “out-of-season” production was considerably less efficient in terms of the N leached per unit of yield, leaching 1.6 to 2 times more N per tonne of harvested product than “in-season” production. Hence, while “out-of-season” production of the study crops may reduce N leaching rates per land area, the overall N leaching associated with meeting consumer demand for “out-of-season” vegetables is likely to be much larger than the N leaching associated with meeting the demand for “in-season” vegetables. As such, whether “out-of-season” production is better or worse for N leaching depends on the perspective taken. The average difference in annual N leaching (as kg N/ha) between the “in-season” and “out-of-season” production regimes were comparable to the reductions achieved through the use of minimum tillage and catch crop GMPs. This supports further research and development of timing-based crop management approaches such as seasonal production in the vegetable cropping industry. No conclusions were able to be made about the financial viability of either “in-season” or “out-of-season” production from the gross margin analysis.
Keywords: 300204 Agricultural management of nutrients